Konsistensi Identitas Visual: Kajian Visual Branding Media Publikasi Borobudur - Muh Ariffudin Islam (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2019)
ABSTRACT Many entities still do not understand the importance of consistently using graphic elements. In the absence of consistency between media, it will create an